Pengaruh Sosialisasi Bahaya Dan Manfaat Listrik Terhadap Kesadaran Masyarakat Desa Torongrejo, Kecamatan Junrejo, Kota Batu - Wicaksono, Ardhitya Bahana Adil; Widarko, Agus; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Torongrejo village, Junjero subdistrict, Batu city is a place where research is conducted. The quantitative research is used type of research . The aim of this research is to determine the effect of socializing the dangers and benefits of electricity on public awareness. The sample used in this research was 40 resident respondents affected by the Sengkaling - Mendalan SUTT / SUTET electricity network in Torongrejo village, Junjero subdistrict, Batu city. Questionnaires are a data collection technique . The results of the research show that socialization about the dangers of electricity does not have a significant effect on public awareness. Meanwhile, socialization of the benefits of electricity and socialization of the dangers and benefits of electricity simultaneously have a significant influence on public awareness. Keywords: Socialization Of The Dangers Of Electricity, Socialization Of The Benefits Of Electricity, And Public Awareness